Analisis Kelimpahan Dan Indeks Saprobitas Fitoplankton Pada Ekosistem Padang Lamun Di Pantai Sindhu, Sanur, Bali - Sang Ayu Made Putri Suryani; Laras Syahrani; I Wayan Arya (Fakultas Pertanian, Universitas Warmadewa, 2022)
Abstract Sindhu Beach is one of the beaches in the Sanur area that is used for various economic activities, such as recreational locations or marine tourism by involving many stakeholders that can affect the aquatic environment which is the habitat of marine biota, is phytoplankton. In addition, the presence of seagrass also affects the abundance and saprobity index of phytoplankton. The research was conducted in May 2021 at Sindhu Beach and the identification process was carried out in the laboratory of the Faculty of Agriculture, Warmadewa University. The method used is the descriptive method. There were 20 types of phytoplankton from five classes, namely Chlorophyceae, Diatomae, Bacillariophyceae, Cyanophyceae, and Dinophyceae classes. The highest abundance of phytoplankton in the third observation was 206.369 ind/l at Station 1 and the lowest at the third observation was 152.866 ind/l at Station 2. At Station 1, the lowest water saprobic index was 0.047 in the first observation, followed by the second observation at 0.130, and the highest at the observation third at 0.307. This value is included in the moderately polluted category. At Station 2, the lowest water saprobic index in the first observation was -0.538, followed by the second observation at 0.28 and the highest at the third observation at 0.523. This value is included in the category of lightly polluted. At Station 3, the lowest water saprobic index in the first observation was 0.307, followed by the second observation at 0.615 and the highest at 0.739. This value is included in the category of lightly polluted.